Analysis Of Risk Factors Causing The Incidence Of Prematurity In Mother With Severe Pre-Eclampsia (Case Study In Permata Bunda Hospital Purwodadi) (Universitas Negeri Semarang, 2018)
Premature labor can increase posibility of infant mortality. Disorders that occur in newborns baby from mothers who suffer from pre-eclampsia can be caused by several factors including maternal age, parity, gestational age, and birth weight of the baby and having a very high risk of complications. The purpose of this study is to analyze the influence of obstetric history, lifestyle and parity in causing the occurrence of premature labor and see the factors that have the most influence in causing the incident. This research is a quantitative study using a case control design with a retrospective approach. The population in this study is mothers with severe pre-eclampsia, sampling is done by using purposive sampling method with 122 respondents divided into two groups, 61 respondents in the case group and 61 respondents in the control group. The results of the study show that parity, lifestyle and obstetric history have a significant effect on the incidence of preterm birth in women with severe pre-eclampsia with p value 0.05. The obstetric history factor has a larger OR of 5,125 compared to other factors, parity with OR 5,102 and a lifestyle of 0.104, therefore it can be concluded that obstetric history has a biggest impact than other variables